A 3D Luminescent Metal‐organic Framework Constructed from Cu4I4 Cubane Clusters and Triangular Imidazole Ligand. Issue 10 (9th May 2014) - Liu, Shan‐Shan; Yuan, Shuai; Hu, Tuo‐Ping; Sun, Di
Abstract Abstract. The solvothermal reaction between cuprous iodide and the rigid triangular imidazole ligand in mixed N, N′‐dimethylacetamide (DMA)‐acetonitrile solvent leads to the isolation of the 3D metal‐organic framework [(Cu4I4)3(TIPA)4]·7DMA (1) [TIPA = tri(4‐imidazolylphenyl) amine], which was characterized by elemental analysis, IR spectroscopy, powder X‐ray diffraction, and single‐crystal X‐ray diffraction. Topologically, the structure of 1 is an unprecedented 3, 3, 4, 4‐connected net with a point symbol of 4.8.1024.82242.82.102284.122. Compound 1 exhibits orange‐red photoluminescence with an emission maximum at 622 nm at room temperature.